Analysis of Gharar and Gambling (Qimar) Elements in Binary Option Transactions on The IQ Option Platform - Baldad Muhammad Syarifati; Qodariah Barkah; Chandra Zaki Maulana (Dinasti Publisher, 2025)
The rapid development of information technology has also provided convenience for people to access various modern financial products. Binary options are one of the financial products that have been familiar, especially in the last decade. Binary options are financial instruments that provide opportunities for clients to gain profit by predicting the price movement of an asset that is determined based on the closing time (expiry time). However, questions then arise regarding the validity of this binary option transaction from a Sharia perspective, whether this transaction is included in those that are permitted or prohibited. This study aims to analyze the transaction mechanism in binary option practices and then analyze the elements of gharar and gambling (qimar) contained in the transaction. This study uses a qualitative method involving a number of approaches, namely the case approach and the conceptual approach with analytical descriptive research specifications. That in this case the author approaches the problem through a review of the provisions of Islamic law regarding the concept of gharar and maysir/qimar and then correlates it with the reality of transactions contained in binary options. The results of the study revealed that the practice of binary options or binary options has been proven to contain elements of gambling and gharar which are forbidden in Islam. In addition, the practice of binary options is contrary to the principles of investment and the principle of justice in modern financial transactions.